2013
DOI: 10.1242/jeb.083881
|View full text |Cite
|
Sign up to set email alerts
|

Survival and arm abscission are linked to regional heterothermy in an intertidal sea star

Abstract: SUMMARYBody temperature is a more pertinent variable to physiological stress than ambient air temperature. Modeling and empirical studies on the impacts of climate change on ectotherms usually assume that body temperature within organisms is uniform. However, many ectotherms show significant within-body temperature heterogeneity. The relationship between regional heterothermy and the response of ectotherms to sublethal and lethal conditions remains underexplored. We quantified withinbody thermal heterogeneity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 70 publications
1
7
0
Order By: Relevance
“…comm.). We further note that none of the temperatures we recorded were close to those found to be stressful in lab and field studies [ 45 47 , 77 80 ]. Although the May 2014 air and water temperatures were higher than average, in previous years similar relatively high temperatures have been reached in most summer months (e.g., Fig 11 , [ 31 , 81 ]) with no evidence of wasting.…”
Section: Discussionsupporting
confidence: 42%
“…comm.). We further note that none of the temperatures we recorded were close to those found to be stressful in lab and field studies [ 45 47 , 77 80 ]. Although the May 2014 air and water temperatures were higher than average, in previous years similar relatively high temperatures have been reached in most summer months (e.g., Fig 11 , [ 31 , 81 ]) with no evidence of wasting.…”
Section: Discussionsupporting
confidence: 42%
“…NADH dehydrogenase, ATP synthase) in cells and enhanced transcription of genes involved in protein modification, degradation, and apoptosis induction (thrombospondin, ubiquitin ligase, Falconi-anemia group-like protein, protein kinase and tyrosine protein phosphatase) suggest that SSWD affected tissues undergo significant post-transcriptional changes of proteins in response to the disease, in line with observations of lesion formation and tissue degradation. Limb abscission is a common response of echinoderms to stress, including potentially pathogen invasion [ 16 ]. The transcription-level processes leading to autotomy have not been previously described, however they likely involve degradative processes, including the breakdown of extracellular matrices, and possibly the induction of cell death.…”
Section: Resultsmentioning
confidence: 99%
“…The author surmised that the decrease in biomechanical values could be a consequence of a lower probability of linkage reformation, or could indicate the intervention of temperature-dependent hydrophobic interactions (Nemethy, 1988) in the mutability mechanism. Pincebourde et al (2013) recently showed that in starfish, during aerial exposure at low tide, the incidence of arm autotomy increased when body temperature reached 33 C. Arm loss was consistently more frequent in the hottest examined individuals, thus suggesting that in intertidal echinoderms autotomy (involving irreversible MCT destiffening) could also have an ecological role in avoiding overwarming of the total body, especially of the central disk where vital organs are located. The significance of the effect of temperature on reversible MCT destiffening (as in e.g.…”
Section: Temperaturementioning
confidence: 99%